Capital Mobility, Consumption Substitutability, and the Effectiveness of Monetary Policy in Open Economies - Christian Pierdzioch (Kiel Institute for World Economics (IfW), 2002)
This paper uses a dynamic general equilibrium two-country optimizing model to analyze the consequences of international capital mobility for the effectiveness of monetary policy in open economies. The model shows that the substitutability of goods produced in different countries plays a central role for the impact of international capital mobility on the effectiveness of monetary policy. Paralleling the results of the traditional Mundell-Fleming model, a higher degree of international capital mobility increases the effectiveness of monetary policy only if the Marshall-Lerner condition, which is linked to the cross-country substitutability of goods, holds.
Keywords: F41; F32; F36; 330; Monetary policy; Capital mobility; Internationale Kapitalmobilität; Geldpolitik; Wirtschaftspolitische Wirkungsanalyse; Produktsubstitution; Elastizitätsbedingung; Zwei-Länder-Modell; Offene Volkswirtschaft; Dynamisches Gleichgewicht; Theorie